The Moderating Effect of Female Labor Force Participation on Economic Growth in ASEAN - Tiya Rana Ammara; Sofyan Syahnur; Srinita Srinita (Ekonomikalia Journal of Economics, 2025)
Despite ASEAN’s rapid economic growth, persistent gender gaps in labor participation remained underexplored as determinants of regional development. This study aimed to analyze the effects of gross fixed capital formation, information and communication technology, human capital, labor, and female labor force participation on economic growth in eight ASEAN countries from 2000 to 2023. The Panel Autoregressive Distributed Lag (ARDL) method was employed. Additionally, this study examined the moderating effect of female labor force participation on labor's contribution to economic growth. The estimation results indicated that, in the long run, gross fixed capital formation positively affected economic growth, while information and communication technology and human capital showed positive and negative effects in different models. Labor had a negative and significant effect in the long run. The moderating effect of female labor force participation strengthened the impact of labor on economic growth. The findings of this study highlighted the importance of policies that enhanced human capital quality, developed workforce skills, increased digital literacy, and empowered women to promote sustainable economic growth in the ASEAN region.